Medijska kultura in slovensko slikarstvo - Gnamuš, Nadja (Monitor ISH, 2022)
: In the Slovenian art space, the nineties were a period of specific artistic transition, characterized by the introduction of new cultural and theoretical paradigms. Since the demise of modernist aesthetics, it has been taken for granted that medium-specific innovation was succeeded by re-use and redefinition, autonomy and immanence of artistic form by appropriation and readymade, form by attitude and skill by deskilling. The text discusses the key painterly ideas, which evolved in Slovenian painting within this context. It outlines the specific geopolitical, historical and theoretical contexts, which define the position of Slovenian painting today and points to its major artistic and theoretical influences. The major paradigm shift in recent Slovenian painting was in great deal formulated around the screen as a symbolic form of ”network-society” and the issue of how its mediated visuality and cultural imagery were reflected in painting. The focus is on various forms of influence that a screen exerts on the visual-sensory apparatus of painting, particularly regarding the ways in which painting constructs its representational space in relation to other image-mak-ing techniques and media and its discursive framework. Painting has become a vehicle of inter-media exchange, exploring either the social context of technology, its social and cultural impacts, ideology and the politics of representation, intertwining of art, market and creative industry or is focused on a phenomenology of human-technology relationship.
Keywords: cultural recycling; digitalizacija; digitalization; inter-media exchange; intermedijska umetnost; media culture; medijska kultura; painting; reciklaža; slikarstvo; Slovenija